47.1k views
2 votes
Let an = –3an-1 + 10an-2 with initial conditions a1 = 29 and a2 = –47. a) Write the first 5 terms of the recurrence relation. b) Solve this recurrence relation. Show your reasoning. c) Using the explicit formula you found in part b, evaluate a5. You must show that you are using the equation from part b.

1 Answer

4 votes

We can express the recurrence,


\begin{cases}a_1=29\\a_2=-47\\a_n=-3a_(n-1)+10a_(n-2)7\text{for }n\ge3\end{cases}

in matrix form as


\begin{bmatrix}a_n\\a_(n-1)\end{bmatrix}=\begin{bmatrix}-3&10\\1&0\end{bmatrix}\begin{bmatrix}a_(n-1)\\a_(n-2)\end{bmatrix}

By substitution,


\begin{bmatrix}a_(n-1)\\a_(n-2)\end{bmatrix}=\begin{bmatrix}-3&10\\1&0\end{bmatrix}\begin{bmatrix}a_(n-2)\\a_(n-3)\end{bmatrix}\implies\begin{bmatrix}a_n\\a_(n-1)\end{bmatrix}=\begin{bmatrix}-3&10\\1&0\end{bmatrix}^2\begin{bmatrix}a_(n-2)\\a_(n-3)\end{bmatrix}

and continuing in this way we would find that


\begin{bmatrix}a_n\\a_(n-1)\end{bmatrix}=\begin{bmatrix}-3&10\\1&0\end{bmatrix}^(n-2)\begin{bmatrix}a_2\\a_1\end{bmatrix}

Diagonalizing the coefficient matrix gives us


\begin{bmatrix}-3&10\\1&0\end{bmatrix}=\begin{bmatrix}-5&2\\1&1\end{bmatrix}\begin{bmatrix}-5&0\\0&2\end{bmatrix}\begin{bmatrix}-5&2\\1&1\end{bmatrix}^(-1)

which makes taking the
(n-2)-th power trivial:


\begin{bmatrix}-3&10\\1&0\end{bmatrix}^(n-2)=\begin{bmatrix}-5&2\\1&1\end{bmatrix}\begin{bmatrix}-5&0\\0&2\end{bmatrix}^(n-2)\begin{bmatrix}-5&2\\1&1\end{bmatrix}^(-1)


\begin{bmatrix}-3&10\\1&0\end{bmatrix}^(n-2)=\begin{bmatrix}-5&2\\1&1\end{bmatrix}\begin{bmatrix}(-5)^(n-2)&0\\0&2^(n-2)\end{bmatrix}\begin{bmatrix}-5&2\\1&1\end{bmatrix}^(-1)

So we have


\begin{bmatrix}a_n\\a_(n-1)\end{bmatrix}=\begin{bmatrix}-5&2\\1&1\end{bmatrix}\begin{bmatrix}(-5)^(n-2)&0\\0&2^(n-2)\end{bmatrix}\begin{bmatrix}-5&2\\1&1\end{bmatrix}^(-1)\begin{bmatrix}a_2\\a_1\end{bmatrix}

and in particular,


a_n=\frac{29\left(2(-5)^(n-1)+5\cdot2^(n-1)\right)-47\left(-(-5)^(n-1)+2^(n-1)\right)}7


a_n=\frac{105(-5)^(n-1)+98\cdot2^(n-1)}7


a_n=15(-5)^(n-1)+14\cdot2^(n-1)


\boxed{a_n=-3(-5)^n+7\cdot2^n}

User Assylias
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.